Pengering Cengkeh Menggunakan Oven - Andi Rahmat Saleh; Muhammad Ridwan Agung; L.M. Nuzul Wahyudin; Muhammad Julianto Firdaus (Program Pendidikan Vokasi Teknik Mesin, 2022)
The purpose of this study was to design a clove dryer using an oven. This drying system is with a heat source generated from the heating process using wood waste and to speed up the drying process this machine is assisted with a blower to accelerate the propagation of the heat source throughout the room. To measure the temperature using a temperature of temperature Research on a clove drying device using an oven has been carried out. to measure temperature using temperature. The technique used in this research is the experimental method. The results of the clove drying test have been carried out, the results of the drying of cloves with a time of 180 minutes at a temperature of 81 C° with the results of dry cloves. From the results of the calculation of the temperature on the clove dryer using the oven, it is quite good to use for maximum drying results.